Analysis of Strategic Interactions in the Armenia-Azerbaijan Nagorno-Karabakh Conflict Through the Prism of the Game Theory - Jel’shan N. Medzhidov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2020)
Introduction. The paper attempts to analyze possible and probable strategic moves of the primary and secondary actors in the Armenia-Azerbaijan Nagorno-Karabakh conflict.